Science and Scientification in South Asia and Europe, 1st edition - Michaels, Axel (Routledge India, 2020)
This volume critically examines the role of science in the humanities and social sciences. It studies how cultures and societies in South Asia and Europe underwent a transformation with the adoption or adaptation of scientific methods, turning ancient cultural processes and phenomena into an enhanced scientific structure.